Two Maps of Rainfall. Semiotic Analysis of Data Visualisation - Gužauskas, Sigitas (Semiotika, 2019)
The article offers a comparison of two visual texts, maps which use different means of expression to visualize a single phenomenon, namely the projected change in rainfall in Europe in the period from 2071 to 2100. These are projections of qualitative data that reflect the relation between a natural phenomenon and a particular geographic location. Rainfall described in figures is presented to the viewer via graphic, verbal, and even material means of expres-sion that help create the impression of the phenomenon’s exist-ence. Map 1 (fig. 1) is a visualisation of rainfall on a completely flat surface created mostly through abstract graphic means of expression. Map 2 (fig. 2, 3, 3a) is a three-dimensional installation consisting of a horizontal map, made of moss and their life-support infrastructure. The latter ensures proper dosage of water and light, thus creating a local ecosystem to control the growth of the moss.The semiotic method of analysis is used to disclose and compare the structure of maps of different expression, their plastic dimension as well as elements of the figurative level. Visual semiotic analysis has been employed here to detect the meaning effects created by different means of expression and identify their differences in the signifying process.The analysis opens up with an overview of the plastic dimension which discusses the chromatic, eidetic, topologic, and haptic characteristics of the map surface. Later, the analysis continues with the overview of the figurative level, focusing on the figures and their thematic values.The last stage of the analysis is dedicated to the generalization of the tensions and oppositions of the plastic level and thematic values of the figures as well as consideration and comparison of the peculiarities related to the perception of meaning.The overall analysis leads to the conclusion that in both maps at-tempts are made to represent the data-based natural phenomenon of rain by means of reinstating the rich sensual experience that was abandoned once the phenomenon was reduced to mathematic values. In addition, it is stated in the conclusions that Map 1 is an object where we can observe constructed signifying system, as meanings here are assigned “artificially”, whereas Map 2 consists of figures of the natural world, namely moss, therefore its language is the natural language.
Keywords: data visualisation; visual semiotics; aesthesis; climate change